3D mapping of orientation variation and local residual stress within individual grains of pearlitic steel using synchrotron dark field X-ray microscopy. (May 2021) - Yildirim, C.; Jessop, C.; Ahlström, J.; Detlefs, C.; Zhang, Y.
Abstract: Assessing the local residual stress and orientation with nanometer resolution within embedded steel grains has remained challenging. Here we use an advanced synchrotron technique, dark field X-ray microscopy to map 3D lattice variations, including both the crystallographic orientation and lattice strain, within two pro-eutectoid ferrite grains in pearlitic steel. We found an orientation variation up to 0.5° and compressive elastic strain up to 1.8 × 10 −3 are present in the as-manufactured sample. There is no direct correlation between the measured compressive strain and lattice orientation. The origin of the variations and their influence on the manufacturing process and mechanical properties are discussed. Graphical abstract: Image, graphical abstract